1990
DOI: 10.2105/ajph.80.4.431
|View full text |Cite
|
Sign up to set email alerts
|

A rural outbreak of Legionnaires' disease linked to visiting a retail store.

Abstract: Between May 7 and June 7, 1986, 27 residents of a rural county in Maryland developed legionellosis, and two died. Legionella pneumophila serogroup 1 was cultured from the sputum of two patients and identified in lung tissue of a third patient by direct fluorescent antibody staining. An additional 11 patients had four-fold rises in antibody titer to L. pneumophila, and 13 had single titers greater than or equal to 1:256. To determine risk factors for disease, we performed a case-control study. Twelve of 16 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Case definitions used in outbreak investigations vary [2,7,27]. In our cross-sectional study, 18 % subjects reported symptoms compatible with a sensitive clinical case definition.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Case definitions used in outbreak investigations vary [2,7,27]. In our cross-sectional study, 18 % subjects reported symptoms compatible with a sensitive clinical case definition.…”
Section: Discussionmentioning
confidence: 91%
“…To identify previously unrecognized cases of legionellosis and to confirm the site of environmental exposure, we conducted a cross-sectional study of people who attended the investment seminar at the hotel on the afternoon of 7 April 1993. 27 April, an important public holiday in Australia, and a period which included the Easter holiday. A 10 ml blood sample was collected from each subject, to be tested for antibodies to L. pneumophila.…”
Section: Outbreakmentioning
confidence: 99%
“…It is known that Legionella spp., including SG7 strains, are detected in soil. 13,14 It is probable that the L. pneumophila SG7 strains that contaminated the bathwater adhered to the skin of patients, along with dust from the field. The reason detection was transient may be because the bath has a continuous input of water that overflows freely.…”
mentioning
confidence: 99%
“…The present study found 697 (78%) disease cases and 83 (74%) deaths were associated with Legionella, spp. [16,[18][19][20][21][22][23]25,26,[29][30][31][32][35][36][37][38][39][40][41][42][43][44][45][46]. Other opportunistic waterborne pathogens such as NTM and Sphingomonas, spp.…”
Section: Gap #4: Moving Beyond Legionellamentioning
confidence: 99%